Dietary factors and thyroid dysfunction - Djuričić, Ivana; Todorović, Vanja; Dabetić, Nevena; Zrnić Ćirić, Milica; Ivanović, Nevena; Vidović, Bojana (Archives of Pharmacy, 2022)
Besides iodine deficiency, autoimmune Hashimoto thyroiditis is the leading cause of hypothyroidism globally, characterized by the increased titer of thyroid autoantibodies and destruction of thyroid cells. Graves’ disease is the most common etiology of hyperthyroidism worldwide. Patients with thyroid dysfunction often require dietary modifications. Popular interventions include supplementation with certain vitamins and minerals, as well as trace elements such as iodine and selenium. The intake of food containing goitrogens should be limited. Goitrogens are substances of plant origin that interfere with the production of thyroid hormones, increasing the risk for goiter and hypothyroidism. The primary dietary sources of goitrogens are cruciferous vegetables, soy products, starchy plants, and some fruits. Beyond essential nutrients, there has been an increasing interest in using specific nutraceuticals, including myoinositol, L-carnitine, melatonin, and resveratrol, as potential preventive and therapeutic agents in thyroid diseases. Even though current evidence promotes some beneficial outcomes of these nutraceuticals, further investigations are needed to clarify dose-dependent effects, duration of supplementation, combination in different clinical settings, and the exact mechanism of their action in thyroid disorders.